2003
DOI: 10.1001/archneur.60.12.1740
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Amyloid Precursor Protein Abnormalities in Mild Cognitive Impairment Predict Conversion to Dementia of Alzheimer Type

Abstract: Mild cognitive impairment is a major risk factor for DAT, and Alzheimer disease-related pathological changes can be identified in patients converting to DAT within a 2-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 34 publications
4
38
0
Order By: Relevance
“…Data obtained showed that there was no association between amyloid precursor protein ratios and any specific ApoE allele (Sanchez-Gonzalez et al, 2006). In concordance to previous studies, we observed a significant decreased amyloid precursor protein ratio on AD subjects as compared to that of control subjects (Utermann, 1987;Borroni et al, 2003). This means that an increased degradation of this precursor protein is being performed in peripheral tissues.…”
Section: Amyloid Precursor Proteinsupporting
confidence: 90%
“…Data obtained showed that there was no association between amyloid precursor protein ratios and any specific ApoE allele (Sanchez-Gonzalez et al, 2006). In concordance to previous studies, we observed a significant decreased amyloid precursor protein ratio on AD subjects as compared to that of control subjects (Utermann, 1987;Borroni et al, 2003). This means that an increased degradation of this precursor protein is being performed in peripheral tissues.…”
Section: Amyloid Precursor Proteinsupporting
confidence: 90%
“…Among those, platelet forms of amyloid precursor protein have been proposed. At two-year follow-up MCI subjects who converted to AD showed a significant decrease of baseline platelet APP forms ratio compared to nonconverters, with a sensitivity of 83% and a specificity of 71% [20].…”
Section: Predictors Of Progression Of MCI To Dementiamentioning
confidence: 93%
“…To this aim, subjects with MCI were enrolled, and were followed up periodically for 2 years, and the progression to dementia was evaluated (Borroni et al, 2003). Interestingly, MCI individuals who progressed to AD showed a significant decrease of baseline platelet APP forms ratio values (mean±SD, 0.36±0.28) when compared with stable MCI subjects (0.73±0.32, P<.01) and patients who developed other types of dementia (0.83±0.27, P=.03) (see Figure 2 and Figure 3).…”
Section: Platelet Amyloid Precursor Protein As a Diagnostic Marker Inmentioning
confidence: 99%
“…By fixing a cutoff score of 0.6, the sensitivity of APP ratio marker in detecting preclinical AD was 83%, while the specificity was 71%. This study suggested that alteration of platelet APP forms is an early event in AD, antedating clinical symptoms up to at least two years, and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 that the measurement of APP ratio may be useful for the identification of preclinical AD in subjects with MCI (Borroni et al, 2003). This is in line with the general knowledge that biological changes antedate the onset of symptoms in neurodegenerative disorders.…”
Section: Platelet Amyloid Precursor Protein As a Diagnostic Marker Inmentioning
confidence: 99%